Blessing Nonvital Tooth with Life through Revascularization - Jain, Ankur; Tyagi, Parimala; Bansal, Arpana; Tiwari, Utkarsh (Journal of Orofacial Research, 2015)
In recent times, revascularization has been found to be a better alternative in treatment of immature, nonvital tooth with blunderbuss canal since, it enables formation of root apex radiographically which allows the clinician to get a better hermeatic seal in the apical area. Success of the treatment also dependsgreatly upon the disinfection of the canal, which is achieved not only by the use of intracanal irrigants, but also with the use of intracanal medicaments like triple antibiotic paste, which is followed by getting a good coronal seal to prevent orthograde infection during the procedure. However, long-term prognosisof the treatment and the tissue occupying the canal space requires further investigation